“INDUSTRIAL MONUMENTS ROUTE OF THE SILESIAN VOIVODESHIP” AS AN EXAMPLE OF INNOVATION AND CHOICE APPROPRIATENESS OF CREATING A CHAIN TOURIST PRODUCT OF A REGION - Jacek Ruszkowski; Włodzimierz Banasik (Acta Scientiarum Polonorum. Oeconomia, 2010)
Te first decade of 21st century is a period of many difficulties and turbulences in the global tourism market. They were caused by further growth of economic globalization and competition on domestic and international markets, global financial crisis and terrorist attacks as well as natural disasters. Tourism also suffered difficulties in Poland, which in 2009 recorded a decrease in activity of domestic tourists and 11% of foreign arrivals by 12%. The way to overcome difficulties in the tourism industry and maintain its position in the highly competitive domestic and international market is innovation in creating innovative and attractive tourism products, ensuring their high quality, which will build their brands so that they could become a symbol of a region, attracting domestic and foreign issues. Development of regional tourism brand-building is an effective way to its promotion and to increase economic mobilization of local communities. The paradigmatic example of this approach is “The Industrial Monuments Route of the Silesian Voivodeship” as an innovative solution for the creation of a chain tourist product that has become the new image of the region in the country and abroad.